The integration of non-conventional therapeutic modalities in Nursing as a motivating factor for Nursing care - Maria Irene Mendes Pedro Santos; Marta Hansen Lima Basto Correia Frade (Nursing Research, Innovation and Development Centre of Lisbon (CIDNUR) of the Nursing School of Lisbon (ESEL), 2021)
Evidence of the utilization of non-conventional therapeutic modalities by nurses and the outcomes for clients was scarce in Portugal in 2011, when one of the author's primary study took place (Santos, 2011). Data analysis did not address the deep reasons why nurses used complementary/alternative therapies. Objectives: Thus, a new research question: What are nurse's motivations to integrate non-conventional therapeutic modalities in their practice? Method: Interview transcripts and observation records of fifteen nurses, working in Portuguese hospitals, from all types of units of care; and ten nurses and seventeen patients at the pain unit of the Cancer Oncology Institute, was analyzed. Secondary qualitative analysis, using analytic expansion (Thorn, 2013), was conducted. Simplified theoretical model (Burtson and Stichler, 2010) was used as Theoretical Framework. Results: Three themes were identified: Nursing care values; Knowledge base; Acting according to values and knowledge base. There is also evidence of the impact of promoters (compassion satisfaction and nurse job satisfaction) of nurse caring. Discussion: The meanings of action and the need for a trusting relationship are key elements of nursing care. Nurses are motivated to care by the satisfaction they derive from caregiving, as Burston & Strichler (2010) state. Interaction opportunities, praise and recognition, and compassion satisfaction, all of them are promoter's factors of nursing job satisfaction. Further research is needed to confirm the impact of care promoters in different cultures and measure the factors of nursing care, to support changes in nursing practice.